Simulación del tráfico en una vía expresa y análisis estadístico de los resultados - Torres Vega, Pedro Jesús (2012)
The increasing number of vehicles produces serious bottlenecks problems in urban areas; this situation generates questions about the variables control methods of interest in this problem. The study case presents an approach to the topic and is based on a hypothetical scenario (expressway), which it models and simulates with a microscopic approach, considering the individual movement of vehicles. It presents a methodology to perform the statistical analysis of the simulation results.